Chondroplasty Efficacy of Bone Matrix - Yu.M. Iryanov; N.A. Kiryanov (International Journal of Human Anatomy, 2019)
Aim To study the chondroplasty efficacy of the bone matrix obtained using an original technology in restoring cartilage defect of the knee joint. Material and Methods Marginal defects were modeled on the surface of the distal end of the femur in 40 adult male Wistar rats. The bone matrix obtained using an original technology was implanted in the damaged area in animals of the experimental group. Material was investigated by means of light microscopy, transmission and scanning electron microscopy, and electron probe X-ray microanalysis. Results It was found that the bone matrix implanted did not cause an immune rejection reaction, activated reparative chondrogenesis for a prolonged period. In the area of articular cartilage lesion, the regenerate acquiring cellular and histochemical characteristics of the hyaline cartilage tissue was formed. The chondroinductive properties for the bone matrix were ensured by localized growth factors and morphogenetic proteins released during osteoclastic resorption. Conclusion The application of the bone matrix as a stimulator of chondrogenesis is theoretically reasonable and has a good perspective in treatment of damages and diseases of the articular cartilage.
Keywords: articular cartilage defect